A method for etching diamond surface by thermal shock and limited cavity cooperation

CN122771379BActive Publication Date: 2026-10-23HANGZHOU XINYANKE SEMICON MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611232471.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-23
Estimated Expiration
2046-08-14

AI Technical Summary

Technical Problem

铁粉在高温下易发生团聚,难以与金刚石表面形成均匀、充分的接触界面,限制了刻蚀效果的一致性和可控性

Benefits of technology

[0045](1)实现金刚石表面不同晶面的差异化多级刻蚀:本发明得到的刻蚀产物,经SEM观察,{100}晶面呈现蜂窝状多孔结构,{111}晶面呈现大面积层状剥离和撕裂形貌,剥离深度可达数百纳米至数微米。该蜂窝-剥离复合形貌为金刚石与基体的机械锁合提供了较优的界面结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122771379B_ABST
    Figure CN122771379B_ABST
Patent Text Reader

Abstract

The application provides a diamond surface etching method with the cooperation of thermal shock and a limited cavity, and relates to the technical field of superhard material surface treatment. The etching method comprises the following steps: mixing ferrous oxalate and diamond particles, placing the mixture in a crucible, and setting a physical isolation sheet and a carbon powder layer on the mixed powder in sequence after compaction, so that the physical isolation sheet, the carbon powder layer, the inner wall of the crucible and the surface of the mixed powder jointly form a limited cavity; placing the crucible in a constant temperature zone of a tube furnace which has been preheated to a target temperature, and performing rapid thermal shock, so that the ferrous oxalate is decomposed in the limited cavity and reacts with the diamond particles; and cooling after the reaction is completed, so that the etched diamond particles are obtained. The application realizes the differential and multistage etching of the {100} and {111} crystal faces of the diamond by the cooperation of the limited cavity and the rapid thermal shock, the etching effect is remarkable, the process is simple, the cost is low, and the method is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of surface treatment technology for superhard materials, specifically to a method for etching diamond surfaces based on the thermal decomposition of ferrous oxalate and through the synergistic effect of rapid thermal shock and confined cavity. Background Technology

[0002] Diamond, with its extremely high hardness, excellent thermal conductivity, and good chemical stability, has wide applications in various fields such as abrasives, cutting tools, optical windows, and semiconductor devices. However, its high surface chemical inertness results in poor wettability and weak adhesion with matrices such as metals, ceramics, or resins, a limitation that severely restricts the application of diamond in tool materials. To enhance the bonding strength between diamond and the matrix, surface treatments such as plating or etching are usually required to improve interfacial bonding performance. Among these, etching primarily improves bonding strength by increasing surface roughness and enhancing mechanical interlocking.

[0003] Currently, diamond etching mainly includes techniques such as molten salt etching, vapor phase etching, and solid phase etching. Molten salt etching typically places diamond in molten nitrate or phosphate, utilizing the highly reactive oxygen species generated to etch the surface. However, this method has a slow etching rate, and the molten salt medium tends to leave crystal residues on the diamond surface after the reaction, requiring subsequent acid washing or water bath treatment to remove them, increasing process complexity. Vapor phase etching often uses gases such as air, oxygen, or water vapor to oxidize diamond at high temperatures. This method requires high control of process parameters such as temperature and pressure; fluctuations in these parameters significantly affect the etching rate and surface quality. Furthermore, during scale-up production, ensuring the uniformity of the flow and temperature fields within the furnace is difficult, easily leading to deviations in etching results at different locations. Additionally, vapor phase etching equipment requires large investments and consumes a lot of energy, greatly increasing industrialization costs. Vapor phase etching mainly relies on preferential oxidation of crystal faces, resulting in etching morphologies primarily consisting of triangular or inverted pyramid-shaped corrosion pits. Such uniformly distributed corrosion pit structures are difficult to form the inverted anchor points required for mechanical interlocking. Solid-phase etching primarily relies on the solid-state reaction between iron, cobalt, nickel, or their oxides and carbon on the diamond surface at high temperatures to dissolve and remove the carbon. This method is relatively simple, requiring no complex molten salt or gas-phase equipment, and is currently the main industrially applied technology in the field of diamond surface treatment. However, existing solid-phase etching processes often use elemental iron powder as the etchant. Iron powder tends to agglomerate at high temperatures, making it difficult to form a uniform and sufficient contact interface with the diamond surface, limiting the consistency and controllability of the etching effect. Furthermore, the amount of iron powder required for etching diamond is as high as 5 to 10 times its mass, and a large amount of iron powder remains on the diamond surface in elemental or oxide form after the reaction, requiring acid washing for removal. This not only results in significant waste of raw materials but also significantly increases post-processing costs.

[0004] Therefore, it is necessary to propose a diamond surface etching method that combines thermal shock and confined cavity, aiming to solve the problems existing in the prior art through various improvements. Summary of the Invention

[0005] To achieve the purpose of this invention, we provide a diamond surface etching method that combines thermal shock and confined cavity etching. Ferrous oxalate is decomposed at high temperature to generate etchable elemental iron and its oxides. The synergistic effect of a double-layer confined cavity ("physical isolation sheet + carbon powder") and a rapid thermal shock pushing method effectively protects the in-situ generated elemental iron from oxidation. This achieves differentiated, multi-level etching of the {100} and {111} crystal planes of diamond, resulting in significant etching effects. The process is simple, low-cost, and suitable for industrial production.

[0006] To achieve the above objectives, the technical solution of the present invention is as follows:

[0007] In a first aspect, a method for diamond surface etching that combines thermal shock and confined cavity is provided, comprising:

[0008] Step (a): Ferrous oxalate is mixed with diamond particles to obtain a mixed powder;

[0009] Step (b): Place the mixed powder in a crucible, compact it, and then sequentially place a physical isolation sheet and a carbon powder layer on top of the mixed powder. The physical isolation sheet, the carbon powder layer, the inner wall of the crucible, and the surface of the mixed powder together form a confined cavity.

[0010] Step (c): Place the crucible in the constant temperature zone of a tube furnace that has been preheated to the target temperature and subject it to rapid thermal shock to decompose the ferrous oxalate in the confined cavity and react with the diamond particles in an etching reaction.

[0011] Step (d): After the reaction is complete, the crucible is removed from the constant temperature zone and cooled to obtain etched diamond particles.

[0012] In some embodiments, the ferrous oxalate is ferrous oxalate dihydrate (FeC2O4·2H2O), preferably with a purity greater than or equal to 99 wt%.

[0013] In some embodiments, the diamond particles have a particle size of 50-300 µm. The purity of the diamond particles is ≥99 wt%. Among them, diamonds with a particle size of 100-300 µm are complete single crystal particles, and fine-particle-size diamonds (100 µm and below) are crushed materials.

[0014] In some embodiments, the diamond particles account for 5% to 30% of the total mass of ferrous oxalate and diamond.

[0015] In some embodiments, in step (a), the mixing is carried out using a three-dimensional oscillating mixer with a mixing speed of 150-200 r / min and a mixing time of 12-24 h. During the mixing process, the ratio of the total mass of the mixed powder to the mass of the agate grinding ball is 1:(10-20), and the diameter of the grinding ball is 6-10 mm.

[0016] In some embodiments, compaction refers to compacting the mixed powder with a spoon or a grinding rod.

[0017] In some embodiments, the crucible has a purity of ≥99wt% and is made of corundum or quartz.

[0018] In some embodiments, in step (b), the physical separator is a sheet material that is chemically inert at 1000°C and above, selected from graphite paper or alumina sheets. In some embodiments, the thickness of the physical separator is 0.5–3 mm. In some embodiments, the purity of the physical separator is ≥99.9%. In some embodiments, the size of the physical separator matches the inner diameter of the crucible, allowing it to completely cover the surface of the mixed powder and be secured to the crucible wall, forming a physical capping structure that prevents external oxygen from directly diffusing into the interior of the mixed powder.

[0019] In some embodiments, the carbonaceous powder is selected from any one or more of carbon black, activated carbon, and charcoal.

[0020] In some embodiments, commercially available industrial-grade carbon black may be used, and the activated carbon and charcoal need to be pulverized to a particle size of no more than 200 mesh (≤74 µm). In some embodiments, the thickness of the carbonaceous powder layer is 3~5 mm, and the purity of the carbonaceous powder is no less than the industrial grade standard.

[0021] In some embodiments, the tubular furnace is provided with tube plugs at both ends to assist in the formation of an instantaneous high-concentration reducing atmosphere during rapid thermal shock, and the heat treatment atmosphere is air.

[0022] In some embodiments, the target temperature is 980~1100°C.

[0023] In some embodiments, the crucible is rapidly pushed into the isothermal zone of a tube furnace that has been preheated to the target temperature, with a pushing time of 5 to 15 seconds.

[0024] In some embodiments, the holding time for the etching reaction is 30-60 minutes. Holding at this temperature for a certain time ensures that ferrous oxalate is fully decomposed into elemental iron, which then reacts with the diamond particles to achieve the desired etching effect.

[0025] In some embodiments, the cooling is performed by rapidly pulling the crucible to the cold end of the tube furnace for natural cooling.

[0026] In some embodiments, the cold end temperature of the tubular furnace is below 300°C.

[0027] In some embodiments, the method further includes a post-treatment step of acid washing and drying the cooled diamond particles.

[0028] In some embodiments, the pickling is performed using an oxalic acid solution with a concentration of 10-20 wt%, a temperature of 60-70°C, and a treatment time of 18-24 hours. In some embodiments, the diamond particles are rinsed with deionized water after pickling.

[0029] In some embodiments, the drying temperature is 70~90°C and the processing time is 1~4 hours.

[0030] In some embodiments, the crucible is configured to be rapidly pushed into the isothermal zone to achieve rapid thermal shock, causing the ferrous oxalate to decompose within the confined cavity to generate elemental iron and its oxides, which then react with the diamond particles in an etching reaction.

[0031] In some embodiments, the physical isolation sheet is graphite paper or alumina sheet, and the carbonaceous powder layer is any one or more of carbon black, activated carbon, or charcoal.

[0032] In a second aspect, a diamond particle obtained by the etching method described in this invention is provided, wherein the {100} crystal facet of the diamond particle exhibits a honeycomb porous structure, and the {111} crystal facet exhibits a layered peeling and tearing morphology.

[0033] In some embodiments, "room temperature" or "room temperature" refers to 10~40°C, preferably 20~30°C or 25°C.

[0034] like Figure 1 As shown, the etching mechanism of the present invention is as follows:

[0035] First, ferrous oxalate dihydrate undergoes a thermal decomposition reaction at high temperatures. When a crucible containing a mixture of ferrous oxalate and diamond powder is rapidly pushed into the isothermal zone of a high-temperature tube furnace, the ferrous oxalate reaches its decomposition temperature within seconds, undergoing the following reaction:

[0036] FeC2O4·2H2O→ FeC2O4+2H2O

[0037] FeC2O4 → FeO + CO↑ + CO2↑

[0038] FeO + CO → Fe + CO2↑

[0039] Rapid thermal shock causes the above decomposition reaction to occur violently within a very short time, generating large amounts of CO and CO2 gases. Combined with the plugs at both ends of the tubular furnace and the semi-enclosed structure of the furnace itself, these gases rapidly accumulate inside the furnace tubes, forming a momentary high-concentration reducing atmosphere, ensuring that iron in the product exists primarily in its elemental state. Subsequently, the synergistic protective effect of the confined cavity occurs. The double-layered confined cavity of "physical isolation sheet + carbonaceous powder" constructed within the crucible in this invention plays a crucial synergistic protective role:

[0040] (1) Physical barrier: The isolation sheet tightly covers the top of the mixed raw material powder to form a physical capping structure. On the one hand, it prevents external oxygen from diffusing downward into the mixed powder area, creating a low oxygen partial pressure environment for elemental iron produced by the decomposition of ferrous oxalate; on the other hand, it prevents the migration of carbonaceous powder particles caused by airflow disturbance or volatilization at high temperature, preventing them from contaminating the lower raw materials.

[0041] (2) Chemical conversion: The carbon powder layer continuously converts the CO2 produced by the decomposition of ferrous oxalate into CO through the Boudouard reaction (C + CO2 → 2CO), maintaining the reducing atmosphere in the cavity and protecting elemental iron from oxidation. At the same time, the "dome" structure of the separator allows CO2 gas to circulate in the cavity, prolonging the contact time between the gas and the carbon powder layer, and further improving the conversion efficiency of the Boudouard reaction.

[0042] The physical barrier and the carbonaceous powder layer work together and are indispensable: the physical barrier creates a low-oxygen environment for the chemical transformation of the carbonaceous powder, while the chemical transformation of the carbonaceous powder in the carbonaceous powder layer consumes CO2 and generates CO, together ensuring that elemental iron remains in an active state throughout the reaction.

[0043] Finally, the decomposition products, primarily elemental iron (e.g., ferric oxide, magnetite), etch the surface of the diamond particles. Under thermal shock at 1000°C, the elemental Fe generated from the decomposition of ferrous oxalate contacts the diamond surface, catalyzing the surface SP. 3 Carbon becomes SP 2 Graphite-carbon transformation: The in-situ generated active Fe particles bond well with the diamond interface, providing a sufficient interface for solution-precipitation graphitization. C atoms dissolve into the γ-Fe lattice, and graphite precipitates out during cooling due to supersaturation. Under the combined effect of volume effect and cleavage tendency at the interface, the precipitated phase induces lamellar exfoliation and tearing of the diamond {111} crystal plane. SEM observation shows that the surface of the etched diamond particles exhibits rich multi-level etching morphology: the {100} crystal plane is covered with honeycomb-like micron-sized pores, forming a three-dimensional porous structure; the {111} crystal plane exhibits large-area lamellar exfoliation and tearing morphology, with the edges of the lamellae raised, and the exfoliation depth can reach hundreds of nanometers to several micrometers.

[0044] Compared with the prior art, the technical solution provided by the present invention has the following advantages or beneficial effects:

[0045] (1) Achieving differentiated multi-level etching of different crystal planes on the diamond surface: The etching products obtained by this invention, as observed by SEM, show that the {100} crystal plane exhibits a honeycomb porous structure, while the {111} crystal plane exhibits a large-area layered peeling and tearing morphology, with peeling depths reaching hundreds of nanometers to several micrometers. This honeycomb-peeling composite morphology provides a superior interface structure for the mechanical bonding between diamond and the substrate.

[0046] (2) Significantly improved etching effect: Through the synergistic effect of rapid thermal shock and confined cavity, the elemental iron produced by the decomposition of ferrous oxalate is effectively protected in a reducing atmosphere. XRD analysis in Example 1 (e.g.) Figure 2 As shown in section (b), after 60 minutes of heat treatment, the elemental iron peak in the product is extremely strong, while the oxide peak is extremely weak, indicating that most of the iron exists in an active elemental state and participates in the etching reaction. The newly generated iron particles are nanoscale, with high surface activity and significant etching effect. In traditional solid-state etching processes, the iron powder directly added is usually tens of micrometers in size, with coarse particles, low surface activity, and uneven etching reaction on the diamond surface (e.g., Figure 9 (As shown).

[0047] (3) Controllability of the reaction path: This invention achieves a two-stage protection mechanism of "instantaneous CO generation protection → continuous carbon powder supply to maintain CO concentration" through the time-sequential synergy of rapid thermal shock and confined cavity, so that elemental iron is basically not oxidized throughout the entire process from generation to etching and then to the end of heat preservation. This time-sequential synergy mechanism makes the etching process have good controllability and repeatability.

[0048] (4) Simple process and convenient operation: Only the "rapid push-in" operation and the "physical isolation sheet + carbon powder layer" covering structure need to be added to the existing crucible, without the need for additional equipment investment. The ferrous oxalate used is a common industrial raw material, which solves the problems of high cost, waste acid and waste liquid and poor environmental performance of traditional iron-nickel powder etching. The raw material is inexpensive and widely available, and is suitable for industrial promotion and application.

[0049] (5) Wide range of applications: This method is applicable to diamond particles of various sizes (50~300 µm), and can achieve effective etching in the range of 980~1100°C, and exhibits significant crystal plane selective etching characteristics. Attached Figure Description

[0050] Figure 1 This is a schematic diagram illustrating the structure and principle of the diamond surface etching system that combines thermal shock and confined cavity in an embodiment of the present invention.

[0051] Figure 2This is a comparison diagram of the raw materials and products in Example 1 of the present invention. Figure 2 The middle section (a) shows the SEM image of the diamond raw material; Figure 2 Part (b) shows the XRD pattern of the product without diamond particles; Figure 2 The middle (c) section is a SEM image of the diamond particles after etching.

[0052] Figure 3 This is a SEM image of the diamond particles after etching in Example 2 of the present invention.

[0053] Figure 4 This is a SEM image of the diamond particles after etching in Example 3 of the present invention.

[0054] Figure 5 This is a SEM image of the diamond particles after etching in Example 4 of the present invention.

[0055] Figure 6 This is a SEM image of the diamond particles after etching in Example 5 of the present invention.

[0056] Figure 7 The graph shows the correlation between the heat treatment products under different covering conditions in Comparative Example 1. Figure 7 Part (a) shows the XRD patterns of powders that do not contain diamond particles in the products obtained from the three groups of experiments in Comparative Example 1. Figure 7 Part (b) shows the SEM morphology of the diamond particles obtained in group A; Figure 7 Part (c) shows the SEM morphology of the diamond particles obtained in group B; Figure 7 The middle (d) section shows the SEM morphology of the diamond particles obtained in group C.

[0057] Figure 8 The graph shows the products obtained by the furnace heating method in Comparative Example 2. Figure 8 Part (a) shows the XRD pattern of the powder without diamond particles; Figure 8 Part (b) shows the SEM morphology of the diamond particles.

[0058] Figure 9 This is a SEM image of the diamond particles after the iron powder in Comparative Example 3 was etched by heating the furnace.

[0059] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Detailed Implementation

[0060] The present invention will be further illustrated below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not intended to limit the scope of the invention.

[0061] Example 1

[0062] 9 grams of ferrous oxalate (analytical grade) and 1 gram of synthetic diamond single crystal particles with an average particle size of approximately 300 µm and a purity of 99.9 wt% were weighed. The mixture was then mixed for 18 hours using a three-dimensional oscillating mixer at a speed of 180 r / min and a ball-to-particle ratio of 15:1 (agate balls, 8 mm in diameter) to obtain a mixed powder.

[0063] The mixed powder was transferred to an alumina crucible (purity ≥99wt%), with a powder buildup thickness of 5 mm. A layer of graphite paper with a thickness of 1 mm and a purity ≥99.9% was placed on top of the mixed powder; a layer of carbon black powder with a thickness of 4 mm was then placed on top of the graphite paper.

[0064] The tube furnace was heated to 1000°C at a rate of 20°C / min. After the furnace temperature stabilized for 10 minutes, the crucible containing the sample was rapidly pushed into the isothermal zone of the tube furnace within 15 seconds. No protective atmosphere was introduced, and conventional tube plugs were installed at both ends of the tube furnace. The furnace was held at 1000°C for 60 minutes.

[0065] After the heat treatment is completed, the crucible is quickly pulled to the cold end of the tube furnace (temperature below 300°C) using a hook and allowed to cool naturally to room temperature. The resulting product is separated using a sieve, and the separated diamond particles are placed in a 15wt% oxalic acid solution and acid-washed at 65°C with stirring for 24 hours. Subsequently, it is repeatedly rinsed with deionized water and dried in an 80°C oven for 1 hour to obtain the etched diamond particles.

[0066] Diamond raw material image as shown Figure 2 As shown in part (a), its (100) and (111) crystal planes are smooth, and each grain boundary is straight with no obvious defects. Figure 2 Section (b) shows the XRD pattern of the product without diamond particles. Figure 2 As shown in section (b), the diffraction peak intensity of elemental Fe in the product is extremely high, indicating that elemental Fe is the main phase, while the diffraction peaks of Fe3O4 and Fe2O3 are relatively weak. This suggests that under the synergistic protection of rapid thermal shock and confined cavity, most of the iron generated by the decomposition of ferrous oxalate exists in an active elemental state. Figure 2 Section (c) shows the SEM image of the diamond particles. Figure 2As shown in the SEM image in section (c), the surface of the etched diamond particles exhibits significant morphological changes, with the particle edges becoming more rounded and the surface roughness significantly increased. The (111) crystal plane of the etched diamond particles displays a large-area layered peeling and tearing morphology, with the edges of the peeled layers raised and the layer thickness ranging from hundreds of nanometers to several micrometers; while the (100) crystal plane exhibits a dimple-like etching morphology, with dense pits and grooves distributed on the surface, demonstrating obvious selective etching characteristics. This surface structure, with the coexistence of layered peeling and dimple-like morphology, is beneficial for enhancing the mechanical bonding and anchoring effect between the diamond particles and the matrix material.

[0067] Example 2

[0068] Weigh 8.5 g of ferrous oxalate and 1.5 g of crushed synthetic diamond particles with an average particle size of 50 µm and a purity of 99.9 wt%. Mix them for 24 hours using a three-dimensional oscillating mixer at a speed of 150 r / min and a ball-to-particle ratio of 20:1 (agate balls, 6 mm in diameter) to obtain a mixed powder.

[0069] The mixed powder was transferred to an alumina crucible (purity ≥99wt%), with a powder buildup thickness of 6 mm. A layer of graphite paper with a thickness of 0.5 mm and a purity of ≥99.9% was placed on top of the mixed powder; an activated carbon layer (crushed to ≤74µm) with a thickness of 4 mm was then filled on top of the graphite paper.

[0070] The tube furnace was heated to 980°C at a rate of 20°C / min. After the furnace temperature stabilized for 10 minutes, the crucible containing the sample was rapidly pushed into the isothermal zone of the tube furnace within 15 seconds. No protective atmosphere was introduced, and conventional tube plugs were installed at both ends of the tube furnace. The furnace was held at 980°C for 45 minutes.

[0071] After the heat treatment is completed, the crucible is quickly pulled to the cold end of the tube furnace (temperature below 300°C) using a hook and allowed to cool naturally to room temperature. The resulting product is separated using a sieve, and the separated diamond particles are placed in a 10wt% oxalic acid solution and acid-washed at 60°C with stirring for 24 hours. Subsequently, it is repeatedly rinsed with deionized water and dried in an oven at 80°C to obtain the etched diamond particles.

[0072] SEM observation (e.g.) Figure 3 As shown, the original flat crystal faces of the diamond are completely lost after etching, and typical layered cleavage steps of diamond are visible at the grain edges. Locally, the grain surface exhibits continuous, gently sloping dissolution platforms, with a few isolated, shallow elliptical pits distributed on the platform surfaces. Another area shows a deeply etched honeycomb-like porous structure, with numerous micron-sized, unevenly sized pits interconnected to form a three-dimensional network of pores. The pore walls are rough and densely covered with fine, uneven structures.

[0073] Example 3

[0074] Weigh 8 grams of ferrous oxalate and 2 grams of synthetic diamond single crystal particles with an average particle size of 150 µm and a purity of 99.9 wt%. Mix them for 12 hours using a three-dimensional oscillating mixer at a speed of 200 r / min and a ball-to-particle ratio of 10:1 (agate balls, 10 mm in diameter) to obtain a mixed powder.

[0075] The mixed powder was transferred to a quartz crucible (purity ≥99wt%), with a powder buildup thickness of 5 mm. A 1 mm thick layer of alumina flake (purity ≥99.9%) was then placed on top of the mixed powder, followed by a 4 mm thick layer of carbon black.

[0076] The tube furnace was heated to 1000°C at a rate of 20°C / min. After the furnace temperature stabilized for 10 minutes, the crucible containing the sample was rapidly pushed into the isothermal zone of the tube furnace within 5 seconds. No protective atmosphere was introduced, and conventional tube plugs were installed at both ends of the tube furnace. The furnace was held at 1000°C for 60 minutes.

[0077] After the heat treatment is completed, the crucible is quickly pulled to the cold end of the tube furnace (temperature below 300°C) using a hook and allowed to cool naturally to room temperature. The resulting product is separated using a sieve, and the separated diamond particles are placed in a 20wt% oxalic acid solution and acid-washed at 70°C with stirring for 18 hours. Subsequently, it is repeatedly rinsed with deionized water and dried in an 80°C oven to obtain the etched diamond particles.

[0078] SEM observation (e.g.) Figure 4 As shown in the figure, the etched diamond single crystal particles retain their complete blocky outline and exhibit significant selective etching characteristics on crystal faces. Specifically, the {100} crystal facet shows densely distributed honeycomb-like micron-sized etched pits, which interconnect to form a three-dimensional network porosity. The {111} crystal facet exhibits a more severe etching morphology; some surfaces are covered with interwoven network grooves, while others show layered exfoliation structures with raised lamellar edges. The selective etching characteristics on crystal faces are evident. The exfoliation depth is estimated to be approximately 0.5–1.8 µm.

[0079] Example 4

[0080] Weigh 7 grams of ferrous oxalate and 3 grams of synthetic diamond single crystal particles with an average particle size of 300 µm and a purity of 99.9 wt%. Mix them for 20 hours using a three-dimensional oscillating mixer at a speed of 180 r / min and a ball-to-particle ratio of 15:1 (agate balls, 6 mm in diameter) to obtain a mixed powder.

[0081] The mixed powder was transferred to a quartz crucible (purity ≥99wt%), with a powder buildup thickness of 7 mm. A layer of alumina flakes with a thickness of 2 mm and a purity ≥99.9% was placed on top of the mixed powder; a layer of charcoal (crushed to ≤74 µm) with a thickness of 4 mm was then placed on top of the alumina flakes.

[0082] The tube furnace was heated to 1100°C at a rate of 20°C / min. After the furnace temperature stabilized for 10 minutes, the crucible containing the sample was rapidly pushed into the isothermal zone of the tube furnace within 10 seconds. No protective atmosphere was introduced, and conventional tube plugs were installed at both ends of the tube furnace. The furnace was held at 1100°C for 30 minutes.

[0083] After the heat treatment is completed, the crucible is quickly pulled to the cold end of the tube furnace (temperature below 300°C) using a hook and allowed to cool naturally to room temperature. The resulting product is separated using a sieve, and the separated diamond particles are placed in a 15wt% oxalic acid solution and acid-washed at 60°C with stirring for 24 hours. Subsequently, it is repeatedly rinsed with deionized water and dried in an 80°C oven to obtain the etched diamond particles.

[0084] SEM observation (e.g.) Figure 5 As shown in the figure, the etched diamond single crystal particles still retain their complete blocky outline, exhibiting significant selective etching characteristics similar to Example 3. Large-area peeling and tearing occur on the {111} crystal plane, with noticeable lifting of the lamellar edges and a peeling depth of approximately 1.0–3.0 µm. Interwoven network grooves are still visible in localized areas of the surface. The {100} crystal plane still shows densely distributed honeycomb-like micron-sized etched pits. The selective etching characteristics are evident.

[0085] Example 5

[0086] Weigh 8 grams of ferrous oxalate and 2 grams of synthetic diamond single crystal particles with an average particle size of 230 µm and a purity of 99.9 wt%. Mix them for 18 hours using a three-dimensional oscillating mixer at a speed of 180 r / min and a ball-to-particle ratio of 15:1 (agate balls, 8 mm in diameter) to obtain a mixed powder.

[0087] The mixed powder was transferred to an alumina crucible (purity ≥99wt%), with a powder buildup thickness of 8 mm. A layer of graphite paper with a thickness of 2 mm and a purity of ≥99.9% was placed on top of the mixed powder; a layer of carbon black with a thickness of 5 mm was then placed on top of the graphite paper.

[0088] The tube furnace was heated to 1030°C at a rate of 20°C / min. After the furnace temperature stabilized for 10 minutes, the crucible containing the sample was rapidly pushed into the isothermal zone of the tube furnace within 15 seconds. No protective atmosphere was introduced, and standard tube plugs were installed at both ends of the tube furnace. The furnace was held at this temperature for 45 minutes.

[0089] After the heat treatment is completed, the crucible is quickly pulled to the cold end of the tube furnace (temperature below 300°C) using a hook and allowed to cool naturally to room temperature. The resulting product is separated using a sieve, and the separated diamond particles are placed in a 20wt% oxalic acid solution and acid-washed at 70°C with stirring for 20 hours. Subsequently, it is repeatedly rinsed with deionized water and dried in an 80°C oven to obtain the etched diamond particles.

[0090] SEM observation (e.g.) Figure 6 As shown in the figure, the etched diamond single crystal grains retain their complete blocky outlines, and the two types of crystal faces exhibit significantly differentiated selective etching characteristics. Specifically, the {100} crystal face undergoes deep etching, with its surface covered by a network of honeycomb-like micron-sized pores, and a few larger pores; the {111} crystal face exhibits a more severe etching morphology, with some crystal faces covered by interwoven network grooves, and others showing layered exfoliation structures with raised lamellar edges. The selective etching characteristics of the crystal faces are evident.

[0091] Comparative Example 1

[0092] To verify the necessity of the confined cavity structure described in this invention, three sets of comparative experiments were set up, namely:

[0093] Group A: Only a carbon black layer was added without covering the graphite paper (air atmosphere);

[0094] Group B: No overlay added (air atmosphere);

[0095] Group C: No covering layer is added, but an argon protective atmosphere is introduced;

[0096] All other process conditions remained the same as in Example 1. The diamond particle samples obtained under these three conditions were named #1, #2, and #3. XRD phase analysis was performed on the powders that did not contain diamond particles from the products obtained in the above three sets of experiments.

[0097] The results are as follows Figure 7 As shown in section (a), the powder in group A, which does not contain diamond particles, is mainly Fe2O3; the powder in group B, which does not contain diamond particles, is mainly Fe3O4, with a small amount of Fe2O3 and elemental Fe; and the powder in group C, which does not contain diamond particles, is composed of Fe3O4 and Fe2O3. These results indicate that neither the chemical conversion of the carbon black layer alone, nor the external protective atmosphere, nor even complete uncovering, can effectively maintain the metallic state of iron in the decomposition products of ferrous oxalate. Iron is significantly oxidized at high temperatures, and the product is mainly iron oxide. This demonstrates that the physical barrier of graphite paper and the chemical conversion function of carbon black work synergistically and are indispensable; only when both coexist can an effective confined cavity be constructed, achieving the stable existence of elemental iron.

[0098] Further observation of the SEM morphology of diamond particles in the three sets of comparative experiments showed that there were significant differences in etching behavior.

[0099] Group A #1 sample (e.g.) Figure 7 In the sample shown in section (b), the diamond particles suffered severe ablation, with a significant reduction in particle volume. The original smooth surface and straight grain boundaries completely disappeared, replaced by an uneven, rough morphology. Sample #2 of group B (as shown in section (b)) Figure 7 In the sample shown in section (c), the diamond particles largely retain their original crystal shape, with moderate etching at the grain boundaries and numerous triangular indentations ranging from several micrometers to tens of micrometers distributed on each crystal facet. Sample #3 of group C (as shown in section (c)) Figure 7 As shown in section (d), the etching morphology of the diamond is similar to that of sample #2, also characterized by triangular indentations. However, the etching intensity is significantly increased, with the size of the triangular indentations on the crystal surface generally increasing to tens of micrometers. Furthermore, the grain boundaries show severe etching due to the dense accumulation of triangular indentations. It is worth noting that while the triangular indentation morphology in samples #2 and #3 improves the macroscopic roughness of the diamond surface to some extent, its actual effect is negative in terms of enhancing matrix holding power. This is mainly due to two reasons: First, the triangular indentations are caused by preferential etching of the diamond crystal face along a specific crystallographic direction. The pits are inverted triangular pyramids with upward-facing openings and sloping walls, lacking the upturned edge characteristic, and cannot form effective mechanical locking anchors after matrix filling. Second, the sharp indentation tips easily become stress concentration sources during tool service, inducing crack initiation and propagation, thus weakening the strength and service life of the diamond particles. Therefore, triangular scratches only fall under the category of "surface abrasion" and cannot be substantially transformed into effective holding force on the substrate. In contrast, the layered peeling and tearing morphology on the {111} plane in Examples 1-5 of this invention, due to its raised lamellar structure, combined with effective etching on the {100} plane, can provide a multi-level mechanically interlocking interface for the substrate. The two differ fundamentally in their interface strengthening effects. The above XRD and SEM results corroborate each other, consistently showing that effective etching of the diamond surface described in this invention cannot be achieved without physical isolation of graphite paper or by relying solely on an external protective atmosphere. This further confirms the necessity and irreplaceability of the confined cavity structure and the synergistic effect of rapid thermal shock in this invention.

[0100] Comparative Example 2

[0101] To verify the necessity of the rapid thermal shock injection method, a comparative experiment was conducted: The same raw material ratio and "graphite paper + carbon black" confined cavity covering method as in Example 1 were used, but the sample crucible was placed in a tube furnace from room temperature. The tube furnace was heated to 1000°C at a rate of 10°C / min and held at 1000°C for 60 minutes. After the holding period, it was rapidly cooled to room temperature. All other post-processing procedures remained the same as in Example 1.

[0102] XRD phase analysis was performed on the powder containing no diamond particles in the product (e.g. Figure 8 As shown in section (a), the results indicate that the main phase of the product is Fe3O4, with small amounts of Fe2O3 and FeO. This result suggests that during the furnace heating process, the elemental iron produced by the decomposition of ferrous oxalate is gradually oxidized before reaching the effective etching temperature. The confined cavity cannot maintain a sufficient reducing atmosphere during the slow heating process. SEM morphology observation of the etched diamond particles (e.g., ...) was performed. Figure 8 As shown in section (b), the results show that the etching on the diamond surface is very slight: only the (100) crystal facet shows extremely weak pitting corrosion marks, while the (111) crystal facet shows almost no visible changes, and the characteristic large-area layered peeling or tearing morphology shown in Example 1 of this invention is not observed overall. Figure 2 (As shown in section (c)). Macroscopically, the diamond particles obtained in Example 2 are compared with diamond raw materials (such as...). Figure 2 The morphology is similar to that shown in part (a). This result indicates that even with the protection of the finite-domain cavity, the lack of a rapid thermal shock-induced instantaneous high-concentration reducing atmosphere and reaction triggering conditions means that the heat-treated product still cannot achieve effective stripping and etching on the diamond surface.

[0103] In summary, the confined cavity structure can only exert its synergistic protective function when combined with the rapid thermal shock push-in method; both are indispensable and together constitute the necessary conditions for achieving controllable peeling and etching of diamond surfaces.

[0104] Comparative Example 3

[0105] To compare the differences between the in-situ decomposition system of ferrous oxalate described in this invention and the conventional industrial iron powder etching process, a comparative experiment was conducted: The same diamond raw material (average particle size approximately 300 µm) and process parameters (1000°C, holding for 1 hour) as in Example 1 were used. Analytical pure iron powder (53 μm) was used instead of ferrous oxalate as the etchant. The diamond and iron powder (mass ratio 1:10) were mixed and placed directly in a crucible. The same graphite sheets and carbon black were used for confinement protection to prevent oxidation of the iron powder during heating. The furnace temperature was increased (heating rate 10°C / min) to 1000°C. After holding at this temperature, the sample was quickly removed, acid-washed, and the etched diamond sample was obtained.

[0106] SEM observation (e.g.) Figure 9 As shown in the figure, under this conventional process, the diamond {100} crystal facet exhibits a good and uniform etching morphology, similar to the honeycomb structure of the {100} facet in this invention. However, the etching effect of the {111} crystal facet is poor and uneven. In some crystal faces, most areas are not etched, with only a few shallow scratch-like grooves visible locally; some crystal faces show plough-like etching pits and scratches. This result is consistent with the basic understanding of iron powder etching of diamond in industrial practice: the {100} facet is relatively easy to etch, while the {111} facet, due to its stronger chemical inertness, is difficult to effectively and uniformly etch with ordinary micron-sized iron powder. In contrast, Examples 1 to 5 of this invention use ferrous oxalate to decompose in situ at high temperature to generate nano-sized active iron. Combined with the reduction protection of the confined cavity and the instantaneous triggering of rapid thermal shock, the {100} facet is well etched, and the {111} facet is also appropriately and relatively uniformly etched (layered peeling or network grooves). This effectively solves the inherent problems of uneven and insufficient etching on the {111} surface in ordinary iron powder processes.

[0107] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. A method for diamond surface etching combining thermal shock and confined cavity, characterized in that, include: Step (a): Ferrous oxalate is mixed with diamond particles to obtain a mixed powder; Step (b): Place the mixed powder in a crucible, and arrange a physical isolation sheet and a carbon powder layer on top of the mixed powder in sequence. The physical isolation sheet, the carbon powder layer, the inner wall of the crucible, and the surface of the mixed powder together form a confined cavity. The physical isolation sheet is selected from either graphite paper or alumina sheet. Step (c): Place the crucible in the isothermal zone of a tube furnace preheated to the target temperature and subject it to thermal shock, so that the ferrous oxalate decomposes in the confined cavity and reacts with the diamond particles in an etching reaction; the target temperature is 980~1100°C, and push the crucible into the isothermal zone of the tube furnace preheated to the target temperature for 5~15 seconds; Step (d): After the reaction is complete, the crucible is removed from the constant temperature zone and cooled to obtain etched diamond particles.

2. The surface etching method according to claim 1, characterized in that, The ferrous oxalate is ferrous oxalate dihydrate.

3. The surface etching method according to claim 1, characterized in that, The diamond particles have a particle size of 50~300 µm.

4. The surface etching method according to claim 1, characterized in that, The diamond particles account for 5% to 30% of the total mass of ferrous oxalate and diamond.

5. The surface etching method according to claim 1, characterized in that, The mixing is carried out using a three-dimensional oscillating mixer with a mixing speed of 150~200 r / min and a mixing time of 12~24 h.

6. The surface etching method according to claim 1, characterized in that, The crucible has a purity of ≥99wt% and is made of corundum or quartz. The carbonaceous powder is selected from any one or more of carbon black, activated carbon, and charcoal.

7. The surface etching method according to claim 1, characterized in that, The tubular furnace is equipped with tube plugs at both ends to help form a high-concentration reducing atmosphere instantaneously during thermal shock, and the heat treatment atmosphere is air.

8. The surface etching method according to claim 1, characterized in that, The etching reaction is held at a temperature of 30 to 60 minutes.

9. The surface etching method according to claim 1, characterized in that, The cooling process involves pulling the crucible to the cold end of the tube furnace for natural cooling.

10. The surface etching method according to claim 9, characterized in that, The cold end temperature of the tubular furnace is below 300°C.

11. The surface etching method according to claim 1, characterized in that, It also includes post-processing steps such as acid washing and drying of the cooled diamond particles.

Citation Information

Patent Citations

  • Artificial diamond surface etching method

    CN113716560A

  • Diamond etching method for surface nano pore channels

    CN114572979A